The future of paediatric and adolescent gynaecology in Europe. (April 2019) - Stankovic, Zoran B.; Tridenti, Gabriele; Liassides, Marios; Wood, Paul L.; Roos, Eveline J.; ,
Abstract: Paediatric and Adolescent Gynaecology (PAG) is a subspecialty under the umbrella of Obstetrics and Gynaecology but linked to other branches of medicine including Paediatrics, Surgery, Endocrinology and Urology. Therefore future developments in clinical care and education requires a multidisciplinary approach combining aspects of all the above medical specialties, and also with inputs from Public Health, Genetics, Radiology and Psychology. A multidisciplinary collaboration among different specialists is as important as the establishment and adoption of standards in education, training and management. PAG in Europe has evolved from its first steps and it is still growing with the aim of providing increasing protection of the gynaecological and reproductive health of female children and adolescents. In fact, without proper advice and care, inappropriate management of gynaecological issues in childhood and adolescence can be expected to have significant repercussions throughout later years, and into adulthood. The aim of this third paper in this mini-symposium is to explore how PAG should develop in Europe in the near future.